Conducting wine marketing research with impact in China: Guidelines for design, execution and dissemination - Justin Cohen; Larry Lockshin (Wine Economics and Policy, 2017)
China is the fastest growing wine market, but conducting research there is fraught with a variety of issues. This article explores some of the issues the authors have dealt with in conducting wine marketing research in China over the last five years. We discuss issues with the design of research to focus on important issues for both academics and the industry. We relate the key problems in gaining proper translation and useful sampling procedures. Finally, we provide some guidelines for communicating results effectively to different members of the wine trade.
Keywords: 330